The Impact of BTS-GOJEK Sales Promotion on Impulsive Buying Behavior among Indonesian ARMY (BTS Fanbase) - Bryan; Alvin, Silvanus (Open Access Indonesia Journal of Social Sciences, 2023)
Gojek is a start-up company known for its accessibility, facilitated by a practical mobile application that allows users to book various services easily. These services include transportation, food delivery, same-city package delivery, and bill payments through the e-money feature, Gopay. Promotional events involving a collaboration with BTS, a popular K-pop group, have been found to significantly influence impulsive buying behavior in the community. Through the BTS collaboration, Gojek effectively enhances its brand image, particularly among BTS fans, resulting in increased transactions on the Gojek platform. This effect can be attributed to the combination of the collaboration with BTS, attractive promotional offers such as discounts and cashbacks, which successfully capture the attention of the public and prompt impulsive buying behavior. Additionally, Gojek distributes limited edition BTS collaboration merchandise, which further garners the attention of ARMY, the passionate fanbase of BTS. The findings demonstrate the substantial impact of BTS GOJEK event promotion on impulsive buying behavior among Indonesian ARMY, shedding light on the efficacy of collaborative promotional strategies in influencing consumer decisions.